Pelatihan Literasi Membaca Nyaring Berbasis Sinektik Langsung dalam Pendidikan Karakter Anak di Desa Cingambul, Majalengka - Nugraha, Febby Fajar; Sari, Mia Zultrianti; Prasetio, Pajar Anugrah; Satria, Tio Gusti; Gunawan, Agus (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
Pandemic conditions have caused various changes, including in the world of education, in the learning process. Learning that started at school now takes place at home. There are some parents who complain about the difficulty of conditioning their children to be disciplined and willing to study at home with their parents. The impact of studying at home not only affects children's cognitive intelligence, but also aspects of attitude. The method of implementing the service, namely reading aloud training activities, is carried out as a form of anticipation of conditions that are getting worse or even as a solution to improve conditions that are not good. The results of the activity obtained a positive response showing that reading aloud based on direct synectics using fairy tales provides motivation to be enthusiastic about learning, to be a good and responsible child.